Adverse childhood experiences, brain function, and psychiatric diagnoses in a large adult clinical cohort - Keator, David B.; Salgado, Frank; Madigan, Caroline; Murray, Sydnyy; Norris, Stephanie; Amen, Daniel (Frontiers in Psychiatry, 2024)
Adverse childhood experiences (ACEs) have been associated with higher rates of psychiatric illness in adults. Neuroimaging studies have previously identified regional volume, functional connectivity, and altered blood flow as a function of increasing ACEs in relatively small samples. Thus far, no study has evaluated a large adult clinical population to identify which brain functional associations may be mediators between ACEs and an adult psychiatric diagnosis. This study aims to understand the relationship between ACEs and adult brain function in a large clinical cohort (N=7275) using HMPAO SPECT scans at rest and during an attention task (CPT), to gain insight into the common brain functional patterns associated with increasing ACEs in adults with varying degrees of mental health illnesses. We evaluate how patient-reported ACEs are associated with brain function in adults, across diagnoses. We then evaluate the risk of being diagnosed with specific classes of mental health conditions as a function of increasing ACEs, along with understanding which specific ACE questions were statistically related to each diagnosis in this cohort. To evaluate how brain function, in association with ACEs might influence an adult psychiatric diagnosis, we performed mediation analyses where brain functional regions of interest act as mediators between patient-reported ACEs and each diagnosis. Broadly, we found increased function in cognitive control and default mode networks and decreased function in areas of the dorsal striatum and cerebellum. We found that having more ACEs increases the risk of being diagnosed with a variety of mental health conditions that generally fall into anxiety-related disorders, substance abuse-related disorders, and depression. Further, we found many of the regions implicated in the neuroimaging analyses are potential mediators between ACEs and an adult psychiatric diagnosis.